Fatigue Behavior of Textile Composite Materials Subjected to Tension-Tension Loads - Gowayed. Y.; Fan, H.
A model was constructed to evaluate the fatigue behavior of textile composite ma-terials under tension-tension loads. First, traditional FEA was used to evaluate the stiffness reduction and energy release rate due to crack propagation. Results ob-tained from this study were coupled with data on strength degradation of impreg-nated yarns under fatigue loading. Second, stiffness and strength degradation were integrated within a hybrid finite element analysis model, which uses a geometric description of textile composites. An iterative loading procedure was used to apply load and distribute stresses on a unit cell of the textile composites for each fatigue load cycle. Crack initiation and propagation were monitored during each hybrid FE load cycle and strength and stiffness were accordingly degraded. Finally, results obtained from the analytical model were compared to experimental data for 3D angle interlock carbon/epoxy woven composites and showed a good agreement.